The DSB, Corporatization and Coordination - Sørensen, Claus Hedegaard (Proceedings from the Annual Transport Conference at Aalborg University, 2003)
During the last 15 - 20 years reforms inspired by so-called New Public Management have swept the public sector all over the world. This is also the case in the transport sector. One can divide NPM reforms roughly into two groups, reforms regarding internal organisation, and reforms that are interorganisational and regard the organisation of the public service (Klausen and Ståhlberg 1998). This paper deals with interorganisational reforms. Since the mid-1980s what might look like an organisational revolution has taken place in the Danish transport sector. Previously, the Danish state railways (DSB) ran trains as well as the busses and ferries. When the possibilities of building large bridges linking together different parts of Denmark and linking Denmark and Sweden were discussed, they were expected to be state bridges. 88% of the busses in the Greater Copenhagen Area were in-house production by a politically managed company. The sole large airport in Denmark, Copenhagen Airport, was run by Copenhagen Airport Service, which was an administrative unit in the Ministry of Transport. Today, this organisational set-up has been drastically changed. The former state railways has been split into several corporations - some of which have private owners, while others are publicly owned. Two of the large bridges have been built (the third is subject to a decision making process), and the owner of them is a limited company, however the Danish (and the Swedish) State are the only shareholders. Several buss companies nowadays run the busses in the Greater Copenhagen Area and they are all subject to tendering. The Copenhagen Airport today is a limited company quoted on the stock exchange, the state having 33.8% of the shares. Other changes have been seen, but these are probably the most important. In Denmark, the term often used for this process is “corporatization”, this differs from privatisation, because the new corporations are not necessarily private, although regulated according to civil law. “Quangos” is an commonly used – and vague - label for these corporations. Quango is an acronym for “quasi non government organisations” (Barker 1982: 4).